Artificial Inteligent (AI) for future nursing services - Akbar, M Agung (Science Center Group, 2024)
Artificial Intelligence (AI) is transforming nursing services by enhancing decision-making, improving efficiency, and delivering personalized patient care. This article examines the applications, impacts, challenges, and future directions of AI in nursing. Key applications include predictive analytics for patient deterioration, automation of repetitive tasks, and clinical decision support, which collectively reduce workloads and improve care quality. AI also enhances nursing education through personalized learning systems and realistic simulations. Despite its benefits, challenges such as data privacy concerns, algorithmic biases, resistance to technology adoption, and insufficient regulatory frameworks hinder its full implementation. Addressing these challenges requires robust cybersecurity measures, inclusive AI development, comprehensive training programs, and clear guidelines to ensure ethical and effective integration into nursing practices. Looking to the future, advancements such as robotics, natural language processing, and AI-powered chatbots promise to further revolutionize nursing. Collaborative efforts between AI developers and nursing professionals are essential to tailor AI technologies for specific nursing tasks, ensuring relevance and usability. Additionally, incorporating AI training into nursing education will prepare future nurses to adapt to AI-driven healthcare environments. This article highlights the transformative potential of AI in nursing while emphasizing the need for a balanced approach to integration. By addressing barriers and leveraging innovative technologies, AI can enhance nursing services, delivering safer, more efficient, and patient-centered care. The findings underscore AI's role as a complementary tool that supports, rather than replaces, the human aspects of nursing care.